2021
DOI: 10.1002/jmv.26785
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic and its consequences disrupt epidemiology of enterovirus meningitis, South–East France

Abstract: 1929the circulation of several viral pathogens particularly in the pediatric population [7][8][9][10][11][12] and results similar to ours were recently published (data from Minnesota, USA). 13 A better understanding of this phenomenon could help to control more effectively epidemic infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
2
11
0
3
Order By: Relevance
“…We observed a marked decline in the overall incidence and number of AHC cases in 2020 compared to the previous five years in China. Our findings were consistent with the reported declines in other infectious diseases in England, Taiwan, France, and other countries [ 1 , 6 , 9 ]. Recent studies have shown that conjunctivitis could be one manifestation of COVID-19, with an overall rate of 1.1% in COVID-19 patients [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed a marked decline in the overall incidence and number of AHC cases in 2020 compared to the previous five years in China. Our findings were consistent with the reported declines in other infectious diseases in England, Taiwan, France, and other countries [ 1 , 6 , 9 ]. Recent studies have shown that conjunctivitis could be one manifestation of COVID-19, with an overall rate of 1.1% in COVID-19 patients [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…As with the SARS-CoV-2 virus, enteroviruses can be transmitted from person to person by direct or indirect contact or the faecal-oral route, but respiratory transmission can also occur [ 9 ]. During the emergency response to the COVID-19 pandemic, the lockdown of cities, closure of schools, and delayed school opening, followed by a large increase in the proportion of out-of-school children, may have drastically reduced the circulation of AHC-associated pathogens [ 9 ]. Secondly, the implementation of health education promoted students’ hygiene awareness, including wearing masks, hand washing, and social distancing, during the routine and emergency stages [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only the positive rates of respiratory viruses, but also those of enterovirus infection cases, such as HFMD or herpangina, were close to zero in our clinical center, which had never happened for these respiratory viruses in the past 10 years. This phenomenon was demonstrated by a marked decline in the incidence of enterovirus encephalitis following the start of strict COVID-19 quarantine measures, but not only in the incidence of respiratory viruses [ 17 , 18 ]. We also observed a resurgence of cases of respiratory and enterovirus infections after the reopening of schools and communities.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic-related climate change may have an impact on meningitis incidence (Mazamay et al, 2020). Moreover, measures implemented worldwide to mitigate the spread of SARS-CoV2, such as increased use of antiseptics and disinfectants and social distancing, can reduce meningitis incidence (Luciani et al, 2021). On the other hand, the viral infection itself may represent an opportunity for secondary bacterial infections (Singh et al, 2021).…”
mentioning
confidence: 99%